MARITIME EDUCATION IN LATVIA IN HISTORICAL ASPECT - Šimkuva, Helēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Maritime education occupies an important place in the Latvian education system and has a history of more than 230 years.  The aim of the article is to describe the historical development of maritime education in the territory of Latvia and to compare it with the experience of other countries in the field of maritime education. Comparative analysis of maritime education is one aspect of the novelty of the article. In order to conduct research, analyze and evaluate information on the history of the maritime education, the author conducted research in various directions. The methodological basis  is formed by the conception of humanism which is implemented in the social constructionism theory approach. Research methods-1) the study, theoretical analysis and evaluation of scientific, methodological literature and different documents (Kennerley, 2002; Manuel,2017), 2) biographical method, content analysis of documents and biographies. s a result of the research, it has been possible to evaluate Latvian maritime education as an integrated and essential part of the maritime education system of European countries.